INNOVATIVE PLATFORM OF THE AGRICULTURAL SPHERE (Development Service Industry Management, 2024)
The article substantiates the issue of forming a platform for market adaptation of science to crisis conditions and mobilization of scientific potential in breakthrough areas of agricultural development. The possibilities of integration of science and business on the platform of innovative bioeconomy in the crisis economic and legal conditions of Ukraine were evaluated; the bio-ecosystem of the platform and the mechanism of its operation of the partnership of science and business for the implementation of joint innovation and investment projects are substantiated. For the introduction of a well-founded bio-ecosystem, a set of measures is proposed for the formation of a platform in the system of agrarian science on the basis of conducted tests and adopted organizational decisions based on the example of the National Academy of Sciences of Ukraine.A conclusion was made regarding the cooperation of agricultural science and business on the basis of the proposed public-private partnership platform, which will ensure the mobilization of scientific potential to solve the urgent issues of innovative development of agricultural production, rural areas through the creation and transfer of breakthrough and supporting bioinnovations, production of competitive products. innovative agro-food products.
Keywords: agricultural science; agribusiness; platform of innovative bioeconomy; public-private partnership; cluster model of production of innovative products